Viscous methylene blue formulation for antimicrobial photodynamic therapy in dentistry - Carolina Montovam Monteiro; José Marcelo Lacerda Alves Gonçalves; Gabriela Benedito Machado; Orlando Chiarelli-Neto; Renato Araújo Prates; Céline Frochot; Christiane Pavani (Scientific Reports)
Abstract Antimicrobial photodynamic therapy (aPDT) is a promising strategy to combat resistant microbial strains. However, despite its high in vitro efficacy, clinical outcomes often fall short, largely due to insufficient retention of the photosensitizer (PS) at the target site. Factors such as salivary flow and PS aggregation significantly hinder the effectiveness of aPDT. This study presents the development of a high-viscosity methylene blue (MB) formulation tailored for dental aPDT applications. The increased viscosity aims to enhance PS retention at the treatment site, while carefully selected components address MB aggregation, ultimately improving the clinical efficacy of the therapy. Key formulation strategies included the incorporation of a surfactant, anionic polymers, an acidic pH, and reduced MB concentrations to effectively mitigate aggregation. Stability testing demonstrated that the formulation preserved its organoleptic properties, pH, and MB content over 1 year. Although the formulation exhibited lower MB uptake in Candida albicans biofilms compared to aqueous MB, this did not compromise its antimicrobial activity. In vitro aPDT assays showed comparable efficacy between MB in water and the high-viscosity formulation. These findings highlight the potential of the developed viscous MB formulation to enhance the practicality and clinical success of aPDT in dentistry, without compromising its therapeutic effectiveness.